2015
DOI: 10.1038/sj.bdj.2015.853
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of non-phobic and dentally phobic individuals; a secondary analysis of the 2009 Adult Dental Health Survey

Abstract: Participants reporting dental phobia are mostly females, irregular attendees and have a greater treatment need with increased caries levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 29 publications
3
43
3
1
Order By: Relevance
“…e study found that 16.1% of the sample experienced dental phobia, and these prevalence estimates are higher than those reported in the studies of adult patients in other countries. e findings of the Adult Dental Health Survey 2009 in the UK showed that 12.4% of the population had dental phobia [16]. e prevalence of dental phobia ranged from 0.9% to 5.4% in a sample of adult Australians [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…e study found that 16.1% of the sample experienced dental phobia, and these prevalence estimates are higher than those reported in the studies of adult patients in other countries. e findings of the Adult Dental Health Survey 2009 in the UK showed that 12.4% of the population had dental phobia [16]. e prevalence of dental phobia ranged from 0.9% to 5.4% in a sample of adult Australians [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, this comparison shows dental phobia is more common in pregnant women than adult population. Nevertheless, it should be noted that high risk of dental phobia in pregnant women may be related to the female gender [16,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The negative impacts of having dental anxiety in childhood are well recognised, with the potential for lifelong dental anxiety, avoidance behaviours and poor oral health. 8,11 It is therefore encouraging to see a recent emergence of studies involving CBT for children with dental anxiety which have yielded some very positive findings. A qualitative paper, published by a multidisciplinary Swedish group, explored the experiences of dentally anxious 7-19 year olds following 4-15 sessions of CBT with a clinical psychologist.…”
Section: Introductionmentioning
confidence: 99%